KEJAHATAN LINGKUNGAN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Rizky, Fajar Khaify (Ensiklopedia of Journal, 2024)
Abstract: Environmental crimes are crimes as stated in Article 97 of the Law. No. 32 of 2009 concerning Environmental Protection and Management, there are 19 forms of actions that can be subject to criminal legal sanctions. However, in its application, even though the legislation carries the threat of quite severe criminal sanctions, the reality in the field shows that from time to time in provinces, districts and cities, environmental conditions are worrying and cause environmental problems as well as material and immaterial losses. The existence of this case shows the government's inconsistency resulting from weak environmental policies and law enforcement in Indonesia. Therefore, the root of the problem must be sought, whether in terms of incomplete environmental laws and regulations, or whether it is a lack of capacity of the authorities and community compliance with the laws and regulations that apply to environmental protection and management. Therefore, it is necessary to study this research with the aim of studying and understanding environmental crimes, the nature and extent of environmental crimes, types of environmental crimes, and the application of laws and regulations to environmental crimes. The research method used is normative legal research. The results of research on environmental criminal acts in their application include related laws and regulations, including the Law. No. 41 of 1999 concerning Forestry in resolving forest fire crimes and environmental crimes related to mining.Keywords : Environmental Crime, Protection and Environmental Management